Wind capacity growth in the Northwest United States: Cooptimized versus sequential generation and transmission planning. Issue 6 (December 2019) - Maloney, Patrick; Liu, Ping; Xu, Qingyu; McCalley, James D; Hobbs, Benjamin F; Daubenberger, Sara; Johnson, Anders; Williams, Stan
This article demonstrates the benefits of simultaneous cooptimization on a 312-bus network representation of the Western Interconnection power grid with emphasis on The Bonneville Power Administration's operational area in the Pacific Northwest. While generation and transmission expansion planning has traditionally been solved sequentially, simultaneous cooptimization of both guarantees plans at least as cost effective as sequential approaches and better integrates high-quality remote resources like wind into power grids. For three scenarios with varied carbon and transmission costs, results indicate that (1) simultaneous cooptimization provides up to 6 billion dollars in net present value benefits over sequential optimization during the 50-year planning horizon, (2) cooptimization is more adept at tapping into superior remote resources like wind that the sequential approach has trouble identifying for low iterations, and (3) 10 iterations of sequential cooptimization only capture 75%–96% of the transmission benefits of simultaneous cooptimization.